Amino silane coupling agent modified nano SiO2 enhanced bio-based polyamide 56 composite material and preparation method thereof
By using aminosilane coupling agent modified nano SiO2 in bio-based polyamide 56 for melt blending, the problem of slow crystallization of the material in the rapid cooling scenario is solved, and rapid crystallization and stable mechanical properties are achieved.
Patent Information
- Application Number
- CN202510038889.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
AI Technical Summary
Bio-based polyamide 56 crystallizes slowly in rapid cooling scenarios, resulting in mechanical instability and reduced heat resistance, limiting its application.
The modified nano-SiO2 and bio-based polyamide 56 are melt blended by using aminosilane coupling agent. The formation of silicon oxygen bonds reduces hydrogen bonds on the surface of nano-SiO2, improves its dispersion performance, thereby promoting the formation of crystal nucleus and crystallization rate.
The crystallization rate and mechanical properties of bio-based polyamide 56 are significantly improved, ensuring the stability and heat resistance of the material in rapid cooling scenarios.
Smart Images

Figure HSA0000299939590000011 
Figure HSA0000299939590000012 
Figure HSA0000299939590000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to an aminosilane coupling agent modified nano-SiO2 enhanced bio-based polyamide 56 composite material and a preparation method thereof. Background Art
[0002] Polyamide, commonly known as nylon, is polymerized from bio-based pentamethylenediamine and petroleum-based adipic acid. Its components include PA6, PA66, PA56, PA11, etc., with different performance and uses. my country has a large demand for polyamide, but its production technology is restricted by foreign countries. In order to break through the bottleneck, bio-based polyamide 56 was born. Compared with PA66, PA56 is wear-resistant, flame-retardant, has good hygroscopicity, and a fast crystallization rate, but slow crystallization in rapid cooling scenarios leads to mechanical instability and decreased heat resistance, which limits its application.
[0003] It is well known to those skilled in the art that an effective method to increase the crystallization rate and crystallinity is to add a nucleating agent. Among them, nano-SiO2, as an excellent inorganic nucleating agent, can reduce the size of spherulites, promote the formation of crystal nuclei, and increase the crystallization rate. However, nano-SiO2 is prone to agglomeration, which limits its widespread application in PA56. Therefore, improving the dispersibility of nano-SiO2 to further enhance the crystallization performance of PA56 has become the key to research.
[0004] CN116496620A discloses a low-temperature-resistant, high-impact-resistant, and high-flame-retardant polyamide composite material and a preparation method thereof. By adding flame retardants and sarling resin, bio-based polyamide 56 is achieved to have both high flame retardancy and low-temperature impact resistance. CN111087801A discloses a bio-based polyamide 56 material for thermal insulation strips and a preparation method thereof. By adding nucleating agents, glass fibers and other components, the material's crystallization rate is increased and the processing time is shortened.
[0005] In summary, although some patents have explored the modification of bio-based polyamide 56 and the improvement of its crystallization performance, they have failed to solve the problem that PA56 material crystallizes slowly in a rapid cooling scenario, resulting in mechanical instability and decreased heat resistance. Therefore, developing a modified bio-based polyamide 56 with excellent crystallization performance is of great significance for solving the problems existing in the prior art and promoting the further development of bio-based polyamide materials. Summary of the invention
[0006] The purpose of the present invention is to provide a modified bio-based polyamide 56 composite material and a preparation method and application thereof, so as to solve the technical problems of slow crystallization rate and unstable mechanical properties existing in the prior art.
[0007] In order to solve the above technical problems, 1. An aminosilane coupling agent modified nano-SiO2 enhanced bio-based polyamide 56 composite material is characterized in that the modified nano-SiO2 is used for melt blending, and the specific steps are as follows:
[0008] Step 1, drying the bio-based polyamide 56 material at 100-150° C. for 30-40 hours;
[0009] Drying the modified nano-SiO2 at 80-100°C for 10-15h;
[0010] Step 2, fully mixing the modified nano-SiO2 and the bio-based polyamide 56 in a mass ratio of (1-2): 100 to obtain a first mixture;
[0011] Step 3, melt-blending and extruding the first mixture at an extrusion temperature of 250-270° C. to obtain a second mixture;
[0012] Step 4: Dry the second mixture for 10-15 hours to obtain a modified bio-based polyamide 56 composite material.
[0013] Contains aminosilane coupling agent modified nano-SiO2, unmodified nano-SiO2, and bio-based polyamide 56;
[0014] In step 1, the mass ratio of the aminosilane coupling agent to the nano-SiO2 in the aminosilane coupling agent-modified nano-SiO2 is (5-10): 100;
[0015] The aminosilane coupling agent in step 1 is selected from one of 3-aminopropyltrimethylsilane, 3-aminopropyltriethoxysilane, N-(aminoethyl)-aminopropyltrimethoxysilane and diethylenetriaminopropyltrimethoxysilane;
[0016] The preparation steps of modified nano-SiO2 described in step 1 are as follows:
[0017] Step S1, according to the volume ratio of (10-20):72:8, aminosilane coupling agent, anhydrous ethanol and water are mixed in sequence to obtain a dispersible solution;
[0018] Step S2, adding nano-SiO2 to the dispersible solution and performing ultrasonic dispersion for 8-15 minutes to obtain a uniform suspension;
[0019] Step S3, centrifuging the suspension at a speed of 8000-10000 r / min, and drying to obtain the aminosilane coupling agent modified nano-SiO2.
[0020] 7. The content of the aminosilane coupling agent modified nano-SiO2 in step 1 is 1-2% of the mass of the bio-based polyamide 56.
[0021] By adopting the above technical solution, the present invention has the following beneficial effects:
[0022] The present invention provides a bio-based polyamide 56 composite material reinforced by nano-SiO2 modified by an aminosilane coupling agent and a preparation method thereof. The method utilizes the silanol group of the aminosilane coupling agent to form a silicon-oxygen bond with nano-SiO2, effectively reducing the hydrogen bonds on the surface of the nano-SiO2 and improving its dispersion performance. By melt-blending the modified nano-SiO2 with bio-based polyamide 56, the spherulite size is reduced and the formation of crystal nuclei is promoted. The obtained aminosilane coupling agent modified nano-SiO2 reinforced bio-based polyamide 56 composite material exhibits a fast crystallization rate and stable mechanical properties, and has significant beneficial effects. . BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 The flow chart of sample preparation of bio-based polyamide 56 composite material modified by aminosilane coupling agent and nano-SiO2;
[0025] Figure 2 XRD curves of aminosilane coupling agent modified nano-SiO2 modified bio-based polyamide 56 composite material (AMS), unmodified nano-SiO2 modified bio-based polyamide 56 composite material (UMS) and bio-based polyamide 56 (PA56).
[0026] Figure 3 Non-isothermal crystallization curves of PA56, UMS and AMS
[0027] Figure 3 (a) is the non-isothermal crystallization curve of PA56 material;
[0028] Figure 3 (b) is the non-isothermal crystallization curve of the UMS-0.5 sample prepared in Comparative Example 2;
[0029] Figure 3 (c) is the non-isothermal crystallization curve of the UMS-1.0 sample prepared in Comparative Example 2;
[0030] Figure 3 (d) is the non-isothermal crystallization curve of the UMS-1.5 sample prepared in Comparative Example 2;
[0031] Figure 3 (e) is the non-isothermal crystallization curve of the AMS-1 sample prepared in Example 1;
[0032] Figure 3 (f) is the non-isothermal crystallization curve of the AMS-1.5 sample prepared in Example 1;
[0033] Figure 3 (g) is the non-isothermal crystallization curve of the AMS-2 sample prepared in Example 1;
[0034] Figure 4 Isothermal melting and crystallization curves of PA56, UMS and AMS;
[0035] Figure 4 (a) is the isothermal melting crystallization curve of PA56 material;
[0036] Figure 4 (b) is the isothermal melting crystallization curve of the UMS-0.5 sample prepared in Comparative Example 2;
[0037] Figure 4 (c) is the isothermal melting crystallization curve of the UMS-1.0 sample prepared in Comparative Example 2;
[0038] Figure 4 (d) is the isothermal melting crystallization curve of the UMS-1.5 sample prepared in Comparative Example 2;
[0039] Figure 4 (e) is the isothermal melting crystallization curve of the AMS-1 sample prepared in Example 1;
[0040] Figure 4 (f) is the isothermal melting crystallization curve of the AMS-1.5 sample prepared in Example 1;
[0041] Figure 4 (g) is the isothermal melting crystallization curve of the AMS-2 sample prepared in Example 1. DETAILED DESCRIPTION
[0042] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The present invention is further explained below in conjunction with specific implementation modes.
[0044] The preparation method of the aminosilane coupling agent modified nano-SiO2 modified bio-based polyamide 56 composite material provided by the present invention comprises the following specific steps:
[0045] Step 1, according to the volume ratio of (10-20):72:8, aminosilane coupling agent, anhydrous ethanol and water are mixed in sequence to obtain a dispersible solution;
[0046] Add nano-SiO2 to the dispersed solution, and disperse by ultrasonic for 8-15 minutes to obtain a uniform suspension;
[0047] The mass ratio of aminosilane coupling agent to nano-SiO2 is (5-10):100;
[0048] The uniform suspension is centrifuged at a speed of 8000-10000 r / min, and dried to obtain aminosilane coupling agent-modified nano-SiO2 for later use.
[0049] Step 2, drying the bio-based polyamide 56 at 100-150° C. for 30-40 hours; drying the aminosilane coupling agent-modified nano-SiO2 obtained in step 1 at 80° C. for 10-15 hours;
[0050] Step 3, according to the mass ratio of (1-2): 100, the aminosilane coupling agent modified nano-SiO2 and the bio-based polyamide 56 are fully mixed in sequence, melt blended, and extruded;
[0051] Step 4, drying the extruded product for 10-15 hours to obtain an aminosilane coupling agent-modified nano-SiO2-modified bio-based polyamide 56 composite material.
[0052] 5.2 Performance Testing
[0053] 5.2.1 X-ray diffraction (XRD) test
[0054] The D8DISCOVER X-ray diffractometer produced by BRUKER, Germany, was used to perform XRD tests on PA56 and nano-SiO2 / PA56 composites. The test conditions are as follows: the test was conducted at room temperature.
[0055] CuKɑl radiation source: λ = 0.154nm;
[0056] Pressure diffraction angle: 2θ is 5-45°;
[0057] Scanning speed: 10℃ / min;
[0058] Voltage: 40KV;
[0059] Current: 150mA.
[0060] Example 1
[0061] like Figure 1 As shown, this embodiment provides a process flow for preparing an aminosilane coupling agent-modified nano-SiO2-modified bio-based polyamide 56 composite material by using aminosilane coupling agent-modified nano-SiO2.
[0062] Step 1, sequentially taking 20 ml of 3-aminopropyltriethoxysilane, 72 ml of anhydrous ethanol, and 8 ml of water and mixing them to obtain a dispersible solution;
[0063] Add 250 g of nano-SiO2 to the dispersible solution, and disperse by ultrasonic for 10 min to obtain a uniform suspension;
[0064] The uniform suspension is centrifuged at a speed of 10000 r / min, and dried to obtain aminosilane coupling agent modified nano-SiO2 for later use.
[0065] Step 2, drying the bio-based polyamide 56 at 120° C. for 36 hours; drying the aminosilane coupling agent-modified nano-SiO2 obtained in step 1 at 80° C. for 12 hours;
[0066] Step 3, taking 10, 15, and 20 g of the aminosilane coupling agent modified nano-SiO2 obtained in step 2 and mixing them with 3 parts of 1000 g of bio-based polyamide 56 respectively, melt blending, and extrusion molding;
[0067] Step 4, drying the extruded product for 12 hours, to obtain three modified bio-based polyamide 56 composite materials with different proportions of aminosilane coupling agent-modified nano-SiO2 added, and the obtained samples were marked as AMS-1, AMS-1.5, and AMS-2.
[0068] Comparative Example 1
[0069] Step 1: Dry the bio-based polyamide 56 at 120° C. for 36 hours, and the obtained sample is marked as PA56.
[0070] Comparative Example 2
[0071] like Figure 1 As shown, this embodiment provides nano-SiO2 for preparing modified bio-based polyamide 56 fiber.
[0072] Step 1, drying the bio-based polyamide 56 at 120°C for 36 hours; drying the nano-SiO2 at 80°C for 12 hours;
[0073] Step 3, after fully mixing 5g, 10g, and 15g of nano-SiO2 with 3 parts of 1000g of bio-based polyamide 56, melt blending and extrusion molding;
[0074] Step 4, drying the extruded product for 12 hours, to obtain three modified bio-based polyamide 56 composite materials with different proportions of unmodified SiO2 added, and the obtained samples were marked as UMS-0.5, UMS-1, and UMS-1.5.
[0075] like Figure 2 As shown in the figure, samples AMS, UMS and PA56 were taken for XRD comparative analysis. It can be seen that the bio-based polyamide 56 before and after modification showed α crystal form. Compared with the UMS / PA56 composite material, the diffraction peak of the AMS / PA56 composite material showed a slight shift to the left. This phenomenon may be attributed to the unique promotion effect of AMS as a heterogeneous nucleating agent, which further accelerated the formation process of PA56 crystals, resulting in subtle adjustments in the lattice parameters or crystal structure.
[0076] observe Figure 2 In the range of 20° to 25°, we found that AMS and PA56 have similar diffraction peak characteristics within this range. This discovery proves that the introduction of AMS does not change the original crystal form of PA56, and the two have good compatibility at the molecular level. The addition of AMS promotes crystallization while maintaining the basic crystal properties of the PA56 matrix.
[0077] 5.2.2 Non-isothermal crystallization kinetics
[0078] like Figure 3 (a)- Figure 3 As shown in (g), the crystallization performance of the material is verified through non-isothermal crystallization kinetics test.
[0079] Example 2
[0080] Step 1, taking 8-10 mg of each of the three groups of samples obtained in Example 1, placing them in sealed aluminum crucibles; and taking a sealed empty crucible as a control sample;
[0081] Step 2, the whole process was carried out under the protection of high-purity nitrogen at 60 ml / min, the temperature was increased from 20°C to 270°C at a rate of 20°C / min, and stayed at 270°C for 5 minutes to eliminate the thermal history;
[0082] Step 3, then cool down to 30°C at cooling rates of 10, 20, 30, 40, and 50°C / min, respectively, and record the non-isothermal crystallization curve of the polymer.
[0083] Comparative Example 3
[0084] Step 1, take 8-10 mg of each of the three groups of samples obtained in Comparative Example 1, place them in an aluminum crucible and seal them; at the same time, take a sealed empty crucible as a comparison sample;
[0085] Step 2, the whole process was carried out under the protection of high-purity nitrogen at 60 ml / min, the temperature was increased from 20°C to 270°C at a rate of 20°C / min, and stayed at 270°C for 5 minutes to eliminate the thermal history;
[0086] Step 3, then cool down to 30°C at cooling rates of 10, 20, 30, 40, and 50°C / min, respectively, and record the non-isothermal crystallization curve of the polymer.
[0087] Comparative Example 4
[0088] Step 1, take 8-10 mg of each of the three groups of samples obtained in Comparative Example 2, place them in an aluminum crucible and seal them; at the same time, take a sealed empty crucible as a comparison sample;
[0089] Step 2, the whole process was carried out under the protection of high-purity nitrogen at 60 ml / min, the temperature was increased from 20°C to 270°C at a rate of 20°C / min, and stayed at 270°C for 5 minutes to eliminate the thermal history;
[0090] Step 3, then cool down to 30°C at cooling rates of 10, 20, 30, 40, and 50°C / min, respectively, and record the non-isothermal crystallization curve of the polymer.
[0091] Depend on Figure 3 (ag) It can be seen that at a cooling rate of 50℃ / min, all materials have a distinct single crystallization peak, indicating that they can form relatively regular crystals during the crystallization process. When the cooling rate slows down, the crystallization peak shifts to the left and becomes wider, because crystallization requires a certain amount of time for the molecular chains to be arranged in an orderly manner.
[0092] By comparison Figure 3 (bd), UMS / PA56 composites have a gradually widening peak width as the amount of UMS added increases, indicating that the crystallization rate slows down. Figure 3 (eg), it was found that the crystallization phenomenon of AMS / PA56 composite material was opposite to that of UMS / PA56 composite material. As the amount of AMS added increased, the peak width of the crystallization peak gradually narrowed, and the peak width of AMS-2 was the narrowest, and the crystallization rate was the fastest. This is mainly because the amino group of AMS reacts with the amide bond of PA56. When the addition ratio is small, the restriction ability for the PA56 molecular chain is greater than the promotion effect of heterogeneous nucleation, and the crystallization performance is weakened. However, as the amount of AMS increases, the heterogeneous nucleation effect becomes prominent, compensating for the restriction effect and improving the crystallization performance. Therefore, the addition amount of modified nano-SiO2 in the preparation method provided by the present invention is preferably 2%.
[0093] 5.2.3 Isothermal crystallization kinetics
[0094] like Figure 4 (a)- Figure 4 As shown in (g), the crystallization performance of the material is verified by isothermal crystallization kinetics test.
[0095] Example 3
[0096] Step 1, taking 8-10 mg of each of the three groups of samples obtained in Example 1, placing them in sealed aluminum crucibles; and taking a sealed empty crucible as a control sample;
[0097] Step 2 was carried out under the protection of high-purity nitrogen at 60 ml / min throughout the process, with the temperature rising from 20°C to 270°C at a heating rate of 50°C / min, and staying at 270°C for 5 minutes to eliminate the thermal history.
[0098] Step 3, cool down to 224-230°C at a cooling rate of 60°C / min, keep isothermal for 15 minutes to allow the polymer to completely crystallize, and record the isothermal crystallization curve of the polymer.
[0099] Comparative Example 5
[0100] Step 1, take 8-10 mg of each of the three groups of samples obtained in Comparative Example 1, place them in an aluminum crucible and seal them; at the same time, take a sealed empty crucible as a comparison sample;
[0101] Step 2 was carried out under the protection of high-purity nitrogen at 60 ml / min throughout the process, with the temperature rising from 20°C to 270°C at a heating rate of 50°C / min, and staying at 270°C for 5 minutes to eliminate the thermal history.
[0102] Step 3, cool down to 224-230°C at a cooling rate of 60°C / min, keep isothermal for 15 minutes to allow the polymer to completely crystallize, and record the isothermal crystallization curve of the polymer.
[0103] Comparative Example 6
[0104] Step 1, take 8-10 mg of each of the three groups of samples obtained in Comparative Example 1, place them in an aluminum crucible and seal them; at the same time, take a sealed empty crucible as a comparison sample;
[0105] Step 2 was carried out under the protection of high-purity nitrogen at 60 ml / min throughout the process, with the temperature rising from 20°C to 270°C at a heating rate of 50°C / min, and staying at 270°C for 5 minutes to eliminate the thermal history.
[0106] Step 3, cool down to 224-230°C at a cooling rate of 60°C / min, keep isothermal for 15 minutes to allow the polymer to completely crystallize, and record the isothermal crystallization curve of the polymer.
[0107] Depend on Figure 4(ag) It can be seen that at a cooling rate of 50℃ / min, all materials have a distinct single crystallization peak, indicating that they can form relatively regular crystals during the crystallization process. When the cooling rate slows down, the crystallization peak shifts to the left and becomes wider, because crystallization requires a certain amount of time for the molecular chains to be arranged in an orderly manner.
[0108] By comparison Figure 4 (ag) It can be seen that at high temperatures, the crystal nucleus is unstable, the number of nuclei and the difficulty of fixing the molecular chain increase, and the crystallization rate is controlled by the nucleation rate and the crystal growth rate. Therefore, as the crystallization temperature increases, the crystallization peaks of all materials shift to the right, the peak width increases, and the crystallization time is prolonged, indicating that the crystallization rate slows down. Figure 4 (bg) It was found that the crystallization exothermic peak of the UMS series became broader as the addition amount increased, while the opposite was true for the AMS series. Figure 4 (g) It can be seen that the AMS-2 composite material significantly promotes crystallization, the peak becomes narrower, and the time is shortened. This is attributed to the strong heterogeneous nucleation ability of AMS. As the addition ratio increases, the heterogeneous nucleation ability is better than the hindering effect on molecular chain migration, which promotes the crystallization of PA56. Therefore, the addition amount of modified nano-SiO2 in the preparation method provided by the present invention is preferably 2%.
[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An aminosilane coupling agent modified nano-SiO2 enhanced bio-based polyamide 56 composite material and a preparation method thereof, characterized in that: The modified nano-SiO2 is used for melt blending, and the specific steps are as follows: Step 1, drying the bio-based polyamide 56 material at 100-150° C. for 30-40 hours; The modified nano-SiO2 is dried at 80-100°C for 10-15h: Step 2, fully mixing the modified nano-SiO2 and the bio-based polyamide 56 in a mass ratio of (1-2): 100 to obtain a first mixture; Step 3, melt-blending and extruding the first mixture to obtain a second mixture; Step 4: Dry the second mixture for 10-15 hours to obtain a modified bio-based polyamide 56 composite material.
2. According to claim 1, the composite material contains aminosilane coupling agent modified nano-SiO2, unmodified nano-SiO2, and bio-based polyamide 56.
3. The composite material according to claim 1, characterized in that The mass ratio of the aminosilane coupling agent to the nano-SiO2 in the aminosilane coupling agent modified nano-SiO2 is (5-10):
100.
4. According to claim 1, the aminosilane coupling agent is selected from one of 3-aminopropyltrimethylsilane, 3-aminopropyltriethoxysilane, N-(aminoethyl)-aminopropyltrimethoxysilane, and diethylenetriaminopropyltrimethoxysilane.
5. The preparation method according to claim 1, characterized in that: The preparation steps of modified nano-SiO2 described in step 1 are as follows: Step S1, according to the volume ratio of (10-20):72:8, aminosilane coupling agent, anhydrous ethanol and water are mixed in sequence to obtain a dispersible solution; Step S2, adding nano-SiO2 to the dispersible solution and performing ultrasonic dispersion for 8-15 minutes to obtain a uniform suspension; Step S3, centrifuging the suspension at a speed of 8000-10000 r / min, and drying to obtain the modified nano-SiO2.
6. According to claim 1, the content of the aminosilane coupling agent modified nano-SiO2 is 1-2% of the mass of the bio-based polyamide 56.
7. The preparation method according to claim 1, characterized in that: The extrusion temperature of the extrusion molding in step 3 is 250-270°C.
8. The aminosilane coupling agent modified nano-SiO2 enhanced bio-based polyamide 56 composite material and the preparation method thereof according to claim 1, characterized in that: At a cooling rate of 10°C / min, the crystallization rate increased by 135% and the half-crystallization time decreased by 24.4%.
Citation Information
Patent Citations
Bio-based polyamide 56 material for heat insulation strip, preparation method and heat insulation strip
CN111087801A